SYNTHESIS AND CHARACTERIZATION OF MODIFIED MESOPOROUS SILICA-IMOBILIZED Cu(II)-ACETONITRILE COMPLEX AND ITS APPLICATION IN TRANSESTERIFICATION OF FRYING OIL - Syukri -; Rycce Sylviana Pratikha; Novesar Jamarun (Jurnal Riset Kimia, 2014)
Â ABSTRACTMesoporous silica has attracted rapidly growing attention in catalysis. In this work, mesoporoussilica was synthesized by using CTAB surfactant and then modified by AlCl3. Such materialwas used as support for Cu(II)--acetonitile complex and applied in transesterification of fryingoil. The XRD pattern of the obtained silica confirms the availability of chracteristic peak onsilica surface while its TEM exhibits the uniformity of nanochannel of the mesoporous silica.The particle size of silica support has become smaller after grafting process showed by SEMimages. FT-IR spectra of the materials indicated that the Cu(II) grafted on the mesoporoussilica was in the form of its acetonitrile complex. Supprisingly, the Cu loading the graftedcatalyst was found to be very high. That was 21%, when the catalyst applied ontransesterification of the examined frying oil the amount of total methyl ester yielded were of65%.Keywords: mesoporous silica, AlCl3, Cu(II)-acetonitrile complex, transesterification